M-ary overmodulation based on cyclic shift symbols for pilot-free short packet communication scheme - XIU Menglei; DOU Gaoqi; WANG Hao (Tongxin xuebao)
To solve the problem of low transmission efficiency caused by the high overhead of the pilot in the short packet structure, a M-ary overmodulation based on cyclic shift symbol for pilot-free short packet communication scheme was proposed. The scheme adopted cycle code shift keying (CCSK) to modulate pseudo noise (PN) sequences, and used M-ary overmodulation sequences to perform secondary modulation on multiple CCSK symbols. The receiving end utilized the good autocorrelation and cross-correlation characteristics of PN sequences to achieve pilot-free detection and synchronization, which effectively eliminated the training overhead of short packet pilots. The introduction of overmodulation effectively improved symbol synchronization performance while carrying additional information. The synchronization evaluation function of short packet symbols after CCSK and overmodulation was derived, and the feasibility of M-ary overmodulation loading information was verified. Simulation results demonstrate that under AWGN and Rayleigh fading channels, the proposed M-ary overmodulation based on cyclic shift symbols for pilot-free short packet communication scheme for pilot-free short packet communication effectively improves the symbol synchronization performance, and transmits additional lbM bit information compared to a single overmodulation sequence.